Comprehensive analysis of the expression, prognosis, and immune infiltrates for CHDs in human lung cancer - Yang Lv; Wenchu Lin (Discover Oncology, 2022)
Abstract Background The chromodomain helicase DNA-binding (CHD) family, a group of genes that regulate nucleosome spacing and access to transcription factors, contributes to tumorigenesis in various cancers. However, the roles of CHD family members in lung cancer remain poorly understood. Methods We investigated the transcriptional, survival, and immune data of CHDs in patients with lung cancer from the Oncomine, UALCAN, GEPIA, Kaplan–Meier Plotter, TCGA, TIMER, cBioPortal, and CR2Cancer databases. Then, perform functional enrichment analysis of CHDs was performed using the Metascape. Finally, the expression of CHD7, CHD8 and DNA damage response genes were evaluated by quantitative real-time PCR and western blot.The effects of CHD7 or CHD8 knockdown on A549 and PC9 cells were measured in vitro by flow cytometry, cell viability and colony formation assays. Results We found that except for CHD5, nearly all members of CHDs in lung cancer showed altered expression compared with adjacent normal tissues. Moreover, the abnormal expression levels of CHDs were related to the clinical outcome of patients with lung adenocarcinoma and, to a lesser extent, patients with lung squamous cell carcinoma, which were significantly associated with the immune infiltrating levels of immune cells. Furthermore, the functions of CHDs and their neighboring genes are mainly related to DNA repair, the cell cycle, and organelle organization. Finally, cellular experiments conducted in vitro confirmed that CHD7/8 played indispensable roles in DNA damage signaling and cell cycle progression in lung adenocarcinoma cells. Conclusion This study implied that CHD family members, especially in subclass III, are potential targets of precision therapy and new biomarkers for patients with lung cancer.